Phosphorylation of αSNAP is Required for Secretory Organelle Biogenesis in Toxoplasma gondii. (14th December 2015) - Stewart, Rebecca J.; Ferguson, David J. P.; Whitehead, Lachlan; Bradin, Clare H.; Wu, Hong J.; Tonkin, Christopher J.
Abstract : The authors show that phosphorylation of αSNAP, a protein required for turnover of SNARE complexes after vesicle fusion, is important for secretory pathway protein trafficking and organelle biogenesis in Toxoplasma gondii . This work therefore highlights a potential mechanism of regulation of secretory pathway biogenesis during growth in this important pathogen. Abstract : Upon infection, apicomplexan parasites quickly invade host cells and begin a replicative cycle rapidly increasing in number over a short period of time, leading to tissue lysis and disease. The secretory pathway of these highly polarized protozoan parasites tightly controls, in time and space, the biogenesis of specialized structures and organelles required for invasion and intracellular survival. In other systems, regulation of protein trafficking can occur by phosphorylation of vesicle fusion machinery. Previously, we have shown that Toxoplasma gondii αSNAP – a protein that controls the disassembly of cis ‐SNARE complexes – is phosphorylated. Here, we show that this post‐translational modification is required for the correct function of αSNAP in controlling secretory traffic. We demonstrate that during intracellular development conditional expression of a non‐phosphorylatable form of αSNAP results in Golgi fragmentation and vesiculation of all downstream secretory organelles. In addition, we show that the vestigial plastid (termed apicoplast), although reported not to be reliant on Golgi trafficking for biogenesis, is also affected upon overexpression of αSNAP and is much more sensitive to the levels of this protein than targeting to other organelles. This work highlights the importance of αSNAP and its phosphorylation in Toxoplasma organelle biogenesis and exposes a hereto fore‐unexplored mechanism of regulation of vesicle fusion during secretory pathway trafficking in apicomplexan parasites.